ANALISIS MAKNA SIMBOLIK DALAM KAIN TENUN ADAT HELONG DI DESA HANSISI KECAMATAN SEMAU - Virgin Aldian Daek Lusi; Labu Djuli; Samuel H. Nitbani (STKIP Subang, 2026)
This study discusses the symbolic meaning of Helong traditional woven fabric in Hansisi Village, Semau District, Kupang Regency, East Nusa Tenggara Province. Helong woven fabric is one of ther cultural heritagers of ther Helong community that contains cultural, social, and spiritual values passed down from generation to generation. This study aims to describer ther process of making Helong woven fabric and to analyzer ther symbolic meanings contained in its motifs. The theory used in this study is Roland Barthes’ semiotic theory, which includes denotative, connotative, and myth meanings. The method used in this study is a descriptive qualitative method with a field research approach. Data were obtained through observation, interviews, and documentation in Hansisi Village. The results of the study show that the process of making Helong woven fabric is not merely a technical activity, but also contains symbolic values that reflect patience, accuracy, unity, and respect for ancestral cultural heritage. In addition, each motif in Helong woven fabric has its own meaning. The Atuli motif symbolizes unity and togetherness in society, the Apan Klomakia motif symbolizes the harmonious relationship between humans, nature, and God, while the Nenapan motif symbolizes brotherhood and unity in diversity. Based on the results of the study, it can be concluded that Helong traditional woven fabric functions not only as traditional clothing but also as a symbol of the cultural identity of the Helong community, containing moral, social, and spiritual values. Therefore, Helong woven fabric needs to be preserved as part of regional cultural heritage and Indonesia’s national cultural wealth.